Organisational justice, organisational identification and job involvement: the mediating role of psychological need satisfaction and the moderating role of person-organisation fit - Malhotra N.; Sahadev S.; Sharom N.Q. (Routledge, 2024)
Drawing on self-determination theory, this study seeks to account for the influence of perceived organisational justice on employees’ identification with the organisation and job. In particular, the study examines the mediating mechanism of psychological need satisfaction (PNS) in the relationship between the three forms of perceived organisational justice (procedural, distributive and interactional) and organisational identification as well as job involvement. Integrating the P-E fit literature, this study also investigates the under-researched moderating role of person-organisation (P-O) fit. Our findings demonstrate that PNS fully mediates the relationship between perceived justice and organisational identification as well as job involvement. Further, the direct effects of PNS and the indirect effects of perceived justice on both outcomes are found to be stronger when P-O fit is high. Although both distributive and interactional justice are found to influence PNS, the effect of the commonly investigated procedural justice is not found to be significant. Theoretical and practical implications of the study are discussed along with avenues for future research.